Gelatinous peritoneal disease secondary to appendiceal mucinous adenocarcinoma: a case study and review of the literature - Chérihane Dassouli; Fatimaezzahra Aboutarik; Adil Ait Errami; Sofia Oubaha; Zouhour Samlani; Khadija Krati (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
Pseudomyxoma peritonei also referred to as gelatinous ascites, is a rare disorder, described for the first time by R. Wyerth in 1884. It is characterized by the presence of mucous disseminated throughout the peritoneal cavity generally arising from the rupture of an appendicular mucocele. Pseudomyxoma peritonei can be asymptomatic, discovered during a laparotomy. The most common symptom is abdominal distension associated with diffuse abdominal pain. An abdominal CT scan is the most specific diagnostic tool. It shows pathognomonic signs of gelatinous ascites. Mucinous neoplasms of the appendix are the most frequent cause of pseudomyxoma peritonei accounting for 90% of cases. Pseudomyxoma peritonei needs to be considered as a borderline malignant disease because of its inevitable persistence and progression without an adapted therapeutic approach: cytoreductive surgery combined with perioperative intraperitoneal chemotherapy in specialized centers. The principal prognostic factors are the prior surgical history, the completeness of cytoreduction and especially the histopathologic grade. We report the case of pseudomyxoma peritonei secondary to appendiceal mucinous adenocarcinoma.